2021
DOI: 10.3390/v13030528
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Approaches to Dissect Host SUMOylation during Innate Antiviral Immune Responses

Abstract: SUMOylation is a highly dynamic ubiquitin-like post-translational modification that is essential for cells to respond to and resolve various genotoxic and proteotoxic stresses. Virus infections also constitute a considerable stress scenario for cells, and recent research has started to uncover the diverse roles of SUMOylation in regulating virus replication, not least by impacting antiviral defenses. Here, we review some of the key findings of this virus-host interplay, and discuss the increasingly important c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Notably, SUMOylation is a post-translational modification regulating numerous cellular processes 21 . During viral infection, SUMOmediated regulation is involved in the virus replication and host type I interferon responses [53][54][55] . Our study indicated that treatment with global SUMOylation inhibitors resulted in the destabilization of ACE2 and the reduced SARS-CoV-2 infection in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, SUMOylation is a post-translational modification regulating numerous cellular processes 21 . During viral infection, SUMOmediated regulation is involved in the virus replication and host type I interferon responses [53][54][55] . Our study indicated that treatment with global SUMOylation inhibitors resulted in the destabilization of ACE2 and the reduced SARS-CoV-2 infection in cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was designed to identify SUMO2modified proteins and elucidate the cardioprotective mechanisms. SUMOylated proteins were successfully isolated by several strategies including SUMO antibody, an N-terminal tandem affinity protein tag, N-6xHis-SUMO transfection and GST-SIM fusion protein [42][43][44]. In the present study, we introduced the plasmid construct pcDNA3.…”
Section: Discussionmentioning
confidence: 99%